Técnica de la gastrectomía Reichel-Polya en la úlcera gastroduodenal - Christmann, Federico Enrique Bruno (1937)
The author describes a personal technic to carry out a pyloro-gastrectomy for gastro-duodenal ulcer. In twelve stages, the whole operation is realized. The sutures are especially taken care of by aggregating a double perforating plane, in order to secure the impermeability, and haemostasis of the sutures on the stomach and intestine. The study and preparation of the patient as regards, the pre, and post-operative waterbalance requirements have been carried to a maximum simplicity, parallel with the operative technic employed.